2016
DOI: 10.1021/acs.iecr.6b01140
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical ZSM-5 Zeolite Synthesized by an Ultrasound-Assisted Method as a Long-Life Catalyst for Dehydration of Glycerol to Acrolein

Abstract: This paper presents a facile and economical route to synthesizing hierarchical porous ZSM-5 zeolite (HP-ZSM-5) by an ultrasound-assisted method as a long-life catalyst for the glycerol dehydration reaction, which is an important reaction for the sustainable production of acrolein from biobased glycerol. The systematic characterizations indicate that the HP-ZSM-5 catalyst possesses large intracrystal mesopores and abundant accessible acid sites. The ultrasonic treatment and violent stirring play a critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 72 publications
4
37
0
2
Order By: Relevance
“…found that enhancing the amount of mesopores surface area in ZSM‐5 had a major impact on retarding deactivation in the methanol to olefin conversion . Recently, we developed an economical synthesis approach for hierarchical porous ZSM‐5 zeolites by using an ultrasound‐assisted procedure …”
Section: Introductionmentioning
confidence: 99%
“…found that enhancing the amount of mesopores surface area in ZSM‐5 had a major impact on retarding deactivation in the methanol to olefin conversion . Recently, we developed an economical synthesis approach for hierarchical porous ZSM‐5 zeolites by using an ultrasound‐assisted procedure …”
Section: Introductionmentioning
confidence: 99%
“…[1] Glycerol is one of the top-12p latform chemicals, as it can be converted into value-added chemicals. [8] Suprune tal. [3] Ac onsiderable number of studies on the gas-phase dehydration of glycerol over solid acid catalysts have been undertaken.…”
mentioning
confidence: 99%
“…[3] Ac onsiderable number of studies on the gas-phase dehydration of glycerol over solid acid catalysts have been undertaken. [8] Suprune tal. g-Al 2 O 3 is aw ell-known acidic metal oxide, and Kostestkyy et al [5] suggested that g-Al 2 O 3 was more efficient in catalyzingd ehydration reactions than either titania or zirconia, as determined by theory and experiment.…”
mentioning
confidence: 99%
See 2 more Smart Citations